(untitled) (Tanzania Medical Journal, 2015)
This was a retrospective study based on hospital data retrieved from files of patients who were treated at Muhimbili National Hospital (MNH ) for a period of 5 years (2007- 2003). The main objective of the study was to document on surgical removal of impacted wisdom teeth at MNH, Department of Oral Surgery/Pathology. All patients who had been treated and recorded in the files at the department were included in the study. Information regarding age, sex, wisdom tooth removed and location within the jaws were entered on a special data documentation form. The datawere entered into computer software and analyzed by using SPSS computer program. Out of the total 19671 patients who had undergone teeth extractions, about 644(3%) patients underwent surgical removal of impacted wisdom teeth. Of the 644 patients who underwent surgical removal of wisdom teeth, 303 (47.1%) were males and 341 (52.9%) were females. Their sex ratio (M: F) was1:1.13 and their age ranged from 17 to 60 years. The age groups 20-29 [48.1%] and 30-39 [25%] comprised majority of the patients who underwent disimpaction followed by age groups 11-19 [9.4%], 40-49 [11.8%] and 50-59 [5.2%]. Age group 60-69 [0.5%] had fewer patients. A high number of patient 613 [94.2%] with impacted wisdom teeth had their impactions located in the lower jaw whileonly a few number 31[4.8%] located in the upper jaw. The study concluded that majority of patients had their wisdom teeth removed during the age groups 20 – 29 years and 30 – 39 years and the mandible was more commonly affected than the maxilla. Also the study revealed that the prevalence of impacted third molar was low (3.3%) in this local population compared to what has been reported in other studies. The difference couldprobably be due to regional variation of the population and ethnic groups. However there is a need to conduct a prospective study in order to show the real picture of surgery of impacted wisdom teeth within this population.